Rapid Screening Method for Mycobactericidal Activity of Chemical Germicides That Uses Mycobacterium terrae Expressing a Green Fluorescent Protein Gene - Zafer, Ahmed A. (American Society for Microbiology, 2001)
The slow growth of mycobacteria in conventional culture methods impedes the testing of chemicals for mycobactericidal activity. An assay based on expression of the green fluorescent protein (GFP) by mycobacteria was developed as a rapid alternative. Plasmid pBEN, containing the gene encoding a red-shifted, high-intensity GFP mutant, was incorporated into Mycobacterium terrae (ATCC 15755), and GFP expression was observed by epifluorescence microscopy. Mycobactericidal activity was assessed by separately exposing a suspension of M. terrae(pBEN) to several dilutions of test germicides based on 7.5% hydrogen peroxide, 2.4% alkaline glutaraldehyde, 10% acid glutaraldehyde, and 15.5% of a phenolic agent for contact times ranging from 10 to 20 min (22°C), followed by culture of the exposed cells in broth (Middlebrook 7H9) and measurement of fluorescence every 24 h. When the fluorescence was to be compared with CFU, the samples were plated on Middlebrook 7H11 agar and incubated for 4 weeks. No increase in fluorescence or CFU occurred in cultures in which the cells had been inactivated by the germicide concentrations tested. Where the test bacterium was exposed to ineffective levels of the germicides, fluorescence increased after a lag period of 1 to 7 days, corresponding to the level of bacterial inactivation. In untreated controls, fluorescence increased rapidly to reach a peak in 2 to 4 days. A good Pearson correlation coefficient (r ≥0.85) was observed between the intensity of fluorescence and the number of CFU. The GFP-based fluorescence assay reduced the turnaround time in the screening of chemical germicides for mycobactericidal activity to ≤7 days.